Komunikasi Lintas Budaya di Era Digital sebagai Strategi Mengurangi Stereotip terhadap Masyarakat Madura - Rizal, Muhammad Syaiful (Institut Nalanda, 2025)
This study explores how cross-cultural communication in the digital era can serve as a strategy to reduce negative stereotypes against the Madurese community. Stereotypes portraying Madurese people as harsh or aggressive often circulate in digital spaces, reinforcing unfounded prejudices. Using a descriptive qualitative approach, this research involved interviews with ten informants, five Madurese individuals and five non-Madurese individuals who actively use digital media. The findings indicate that digital platforms can serve as effective spaces for fostering intercultural dialogue, offering more accurate representations of Madurese cultural values, and minimizing misunderstandings through digital cultural literacy. However, without proper management, digital media may also amplify harmful stereotypes. Therefore, cross-cultural communication strategies grounded in education, open dialogue, and government-supported policies are essential to cultivating inclusive digital spaces and promoting fairer intercultural understanding. This research highlights the importance of using digital communication to bridge cultural divides and address bias, especially in a diverse and multicultural society like Indonesia.